Educational reforms and secondary school teachers: The weight of the teaching tradition - María Verdeja Muñiz (Arizona State University, 2020)
Despite the changes proposed by different educational reforms that have taken place in the Spanish context during the last 40 years, it is worth asking to what extent the secondary education stage still has more relation with its origins -Plan Pidal, 1857- than with the derivatives of the successive reforms. We made a historical journey through organic laws of education in the Spanish area, focusing our attention on the stage of compulsory secondary education and focusing our reflection on aspects as important as the weight of the teaching tradition. Some principles of educational reforms that have taken place in our country were inspired by a more pedagogic teaching model and not so academic model. It was intended that this educational stage, which is currently mandatory catarter, was a stage to which all the population could access but also could also overcome successfully. However, this model of comprehensive education promulgated by the reforms, is an educational model that has not yet penetrated, with sufficient depth, into the culture of a secondary school teacher who has been trained in a very different teaching tradition and in which today we can see the weight of tradition.